Empowerment and training of students with disabilities in dry cleaning shoe washing business innovation at UPT. PPD Daksa, Pekanbaru - Wahyu Ramadhan; Sabrina Hayati; Yan Hendrika; Nengsi Fitria; Riki Richer; M. Naufal Makarim (Universitas Muhammadiyah Magelang, 2024)
People with disabilities face challenges in obtaining employment due to physical limitations and social stigma. This community service project aimed to enhance the skills of people with disabilities at the Riau Daksa PPD UPT through shoe-washing training (using the dry cleaning method) and soap-making. Twenty-two participants took part, focusing on improving technical skills through hands-on practice and intensive mentoring. The implementation method consists of four stages: a needs assessment, self-acceptance and confidence-building education, dry cleaning technique training, and soap-making training. Evaluation results showed a significant increase in participants' self-acceptance, mastery of dry cleaning techniques (meeting established standards), and soap-making skills. This program successfully empowered people with disabilities by improving their skills and fostering self-acceptance.